Code-Mixing in Agatha Chelsea’s Utterances on Raditya Dika’s YouTube Podcast - Nababan, Sundari Daratista; Pasaribu, Arsen Nahum; Sembiring, Rony Arahta (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2026)
This study aims to analyze the types and contextual patterns of code-mixing in the utterances of Agatha Chelsea on Raditya Dika’s YouTube podcast using Muysken’s (2000) typology. This study employs a descriptive qualitative method. The data consist of 173 utterances containing Indonesian-English code-mixing, collected through documentation and transcription, while data analysis is conducted using coding based on Muysken’s structural classification and contextual observation. The results show that insertion is the dominant type (67.6%), followed by alternation (15.0%) and congruent lexicalization (17.4%). In terms of conversational contexts, insertion functions as a basic strategy across all settings. Alternation appears most frequently in interpersonal and relational contexts, where it marks shifts in perspective. Congruent lexicalization is prominent in academic and scientific discourse as well as in professional and creative practice, reflecting closer structural integration between the two languages. These findings indicate that code-mixing in Agatha Chelsea’s speech is systematic and varies according to conversational context. Abstrak Penelitian ini bertujuan untuk menganalisis tipe dan pola kontekstual campur kode dalam tuturan Agatha Chelsea pada podcast YouTube Raditya Dika menggunakan tipologi Muysken (2000). Penelitian ini menggunakan pendekatan deskriptif kualitatif. Data berupa 173 ujaran yang mengandung campur kode bahasa Indonesia-Inggris dikumpulkan melalui teknik dokumentasi dan transkripsi, sedangkan analisis data dilakukan dengan teknik pengkodean berdasarkan klasifikasi struktural Muysken dan observasi kontekstual. Hasil penelitian menunjukkan bahwa insertion merupakan jenis yang paling dominan (67,6%), diikuti oleh alternation (15,0%) dan congruent lexicalization (17,4%). Dalam konteks percakapan, insertion berfungsi sebagai strategi dasar di seluruh situasi. Alternation paling banyak ditemukan dalam konteks interpersonal dan relasional, berfungsi menandai pergeseran perspektif. Congruent lexicalization muncul secara menonjol dalam wacana akademis dan ilmiah serta praktik profesional dan kreatif, mencerminkan integrasi struktural yang lebih erat antara kedua bahasa. Temuan ini menunjukkan bahwa campur kode dalam tuturan Agatha Chelsea bersifat sistematis dan bervariasi sesuai konteks percakapan.